A matter of time:: a partial test of institutional anomie theory using cross-national time use data - Weld, Dean (Journal of quantitative criminology, 2017)
Objectives The institutional anomie theory of crime (IAT) has traditionally been tested using either survey-based attitudinal measures or government expenditures. However, data on how people use their time may offer more valid and unobtrusive indicators of the theory’s key concepts, since choosing how to spend one’s time is inherently an exercise in expressing values. The present study answers the call for time use data in IAT research. Methods We perform a cross-national test of IAT using data compiled by the Organisation for Economic Co-operation and Development (OECD) from national time use surveys administered in 29 countries since 1999. Using multivariate regression, we assess the relationships between homicide rates and time spent in economic versus noneconomic institutional domains. Results Consistent with prior work, we find mixed support for IAT. By itself, time spent in economic activity is not significantly related to homicide rates. However, the interaction term for time spent in economic and non-economic activities has a positive and statistically significant relationship with homicide, even after controlling for several other factors. Conclusions The results tentatively suggest that non-economic institutions may be criminogenic in some societies. We discuss the importance of our findings and suggest new lines of research to further explore the content of non-economic institutions. We also address other possible applications of time use data in macro-criminological inquiry.